2012
DOI: 10.1242/dev.070813
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau protein in the RPE is essential for normal ocular growth and vascular development

Abstract: SUMMARYMolecular oxygen is essential for the development, growth and survival of multicellular organisms. Hypoxic microenvironments and oxygen gradients are generated physiologically during embryogenesis and organogenesis. In the eye, oxygen plays a crucial role in both physiological vascular development and common blinding diseases. The retinal pigment epithelium (RPE) is a monolayer of cells essential for normal ocular development and in the mature retina provides support for overlying photoreceptors and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Overall, the results indicated that Cre-mediated recombination in retinal neuroprogenitors is not limited to ocular pigmented tissues as originally described (Lange et al, 2012;Mori et al, 2002).…”
Section: Hif2a Is Expressed In Rpe Ganglion Cells Astrocytes and Nesupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, the results indicated that Cre-mediated recombination in retinal neuroprogenitors is not limited to ocular pigmented tissues as originally described (Lange et al, 2012;Mori et al, 2002).…”
Section: Hif2a Is Expressed In Rpe Ganglion Cells Astrocytes and Nesupporting
confidence: 78%
“…As we previously reported a major role for Hif1a regulation in whole eye development by employing the same transgenic line (Lange et al, 2012), we compared eye size and morphology over time and observed no effect ( Fig. S1B,C).…”
Section: Hif2a Is Expressed In Rpe Ganglion Cells Astrocytes and Nementioning
confidence: 63%
“…Difficulty modelling VHL disease in rodents due to embryonic lethality has stunted the progress towards elucidating the molecular mechanisms contributing to retinal hemangioblastoma growth and ultimate vision loss in humans. A conditional RPE-specific Vhl knockout mouse model developed aniridia, microphthalmia, retinal neovascularisation and RPE-specific cell death [25]. Additional deletion of HIF-α resulted in proper iris development and normal ocular growth, suggesting these processes require VHL-dependent regulation of HIF-α in the RPE.…”
Section: Discussionmentioning
confidence: 99%
“…Additional deletion of HIF-α resulted in proper iris development and normal ocular growth, suggesting these processes require VHL-dependent regulation of HIF-α in the RPE. Moreover, Vegf expression and the development of abnormal retinal neovascularisation persisted in the double knockout mouse which suggests a HIF-independent regulation of vascular formation in the mouse retina [25]. .…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α immunohistochemistry was performed in a standardised matter, as previously described [8]. In brief, antigen retrieval was achieved by exposing slides in citrate buffer to 95°C in a steamer for 1 h. Following incubation with a protein block and a blocking agent against endogenous peroxidase, the sections were incubated with primary monoclonal antibodies against HIF-1α (Novus Biologicals ® NB 100-105 diluted in a 1:8000 proportion for SCC/papilloma, 1:4000 for melanoma/nevi and 1:2000 for lymphoma/RLH) for 24 h at 4°C.…”
Section: Immunohistochemistry and Scoringmentioning
confidence: 99%